1991
DOI: 10.1177/0013164491513030
|View full text |Cite
|
Sign up to set email alerts
|

The Grandparent Strengths and Needs Inventory: Development and Factorial Validation

Abstract: Responses for 2,012 Grandparent Strengths and Needs Inventories (GSNI) by grandparents, parents, and grandchildren were factor analyzed to determine if the underlying structure of the instrument fit the hypothesized dimensions suggested by the position of 60 items on six subscales. Two extraction methods, principal components and principal factors analyses, produced 10 factors with prerotation eigenvalues greater than 1.0. A principal component solution set at six factors yielded the "best fit," accounting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Items are scored on a 4‐point Likert scale ranging from always to never. Construct validity of this instrument has been supported by factor analysis (Collinsworth et al. 1991).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Items are scored on a 4‐point Likert scale ranging from always to never. Construct validity of this instrument has been supported by factor analysis (Collinsworth et al. 1991).…”
Section: Methodsmentioning
confidence: 94%
“…1991). Internal consistency reliability for the subscales range from 0.82 to 0.93, and test–retest correlations for subscales range from 0.70 to 0.85 (Collinsworth et al. 1991).…”
Section: Methodsmentioning
confidence: 99%
“…A factor analysis involving responses from 2,000 inventories representing culturally diverse grandparents, parents, and grandchildren determined that the underlying structure matches the hypothesized dimensions suggested by position of 60 items of six scales. A solution set at six factors yielded the best fit, accounting for 49% of the variance (Collinsworth, Strom, Strom, & Young, 1991;Strom & Strom, 1993). …”
Section: Reliability Validity and Translationmentioning
confidence: 99%
“…A factor analysis of responses of 2,012 inventories from culturally-diverse grandparents, parents, and grandchildren found that the underlying structure of the GSNI matches the hypothesized dimensions suggested by position of 60 items of six scales. A solution set at six factors yielded (Collinsworth, Strom, Strom, & Young, 1991).…”
Section: Reliability and Validity Of The Gsnimentioning
confidence: 99%